Common genetic polymorphisms define one-carbon metabolite responses to different forms of choline in healthy adult males - Butt, Nisa; Dong, Jianzhang; Shelp, Gia V.; Poole, Elizabeth M.; Keathley, Justine R.; Bakovic, Marica; Cho, Clara E. (Frontiers in Nutrition, 2025)
BackgroundResponsiveness to nutrients can be determined by many types of variations, such as single-nucleotide polymorphisms (SNPs). Choline is an essential nutrient critical for proper organ function and exists in different forms, such as free choline or as derivatives, including phosphatidylcholine (PC). Although genetic variations in genes encoding enzymes that influence choline metabolism have been identified, little is known regarding individual responses to free choline and PC in relation to SNPs. Here, we determined the effect of different forms of choline, genotype, and their interaction on one-carbon metabolite concentrations in urine, which has utility in capturing the overall change in choline metabolism.MethodsA randomized, double-blinded, crossover study was conducted in healthy adult males (n = 37) who were provided with a standardized meal containing 600 mg choline, either as choline bitartrate (CB) or PC, or no choline (NC). Urine was collected at study baseline and pooled throughout the 6-h study duration. Choline dehydrogenase (CHDH) rs12676, betaine-homocysteine S-methyltransferase (BHMT) rs3733890, choline kinase alpha (CHKA) rs10791957, and phosphatidylethanolamine N-methyltransferase (PEMT) rs4646343 were genotyped.ResultsThere was a main treatment effect for urinary choline change from baseline, reflective of differences in absorption by free choline versus PC (p < 0.01). A reduction in responsiveness to CB was found with genetic variation in CHDH rs12676, manifested as lower choline oxidation (p < 0.05), and downstream pathways in the methionine cycle (p < 0.01), whereas a reduction in responsiveness to PC occurred with genetic variation in BHMT rs3733890 (p < 0.05). Genetic variations in CHKA rs10791957 and PEMT rs4646343 reflected differences in the partitioning of choline in response to CB and PC (p < 0.01). Multivariate analysis showed that groups with an accumulated number of effect alleles across all SNPs have contrasting responses to CB and PC that deviate from the patterns derived from treatment effect alone (p < 0.05).ConclusionUnique metabolite signatures in one-carbon metabolism arise in response to supplemental intake of different forms of choline, driven by genetic variations that regulate choline homeostasis. Our findings highlight the importance of nutrient–gene interactions in deciphering the complexity of individual metabolic responses, supporting the emerging concept of precision nutrition.